Notch signaling: An emerging therapeutic target for cancer treatment. Issue 1 (1st December 2015) - Yuan, Xun; Wu, Hua; Xu, Hanxiao; Xiong, Huihua; Chu, Qian; Yu, Shiying; Wu, Gen Sheng; Wu, Kongming
Highlights The Notch signaling pathway is commonly activated in cancer and its activation plays key role in the progress of cancer. Pharmacological inhibitors of this pathway can overcome chemoresistance. Notch inhibitor alone or in combination with chemotherapeutics is clinically evaluated on some cancer.